(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
This paper has as a starting point the ecological and social crisis linked to the expansive dynamics of capitalism. We wonder if there is some room in the business management arena to deal with this global challenge. An argumentative style is used to defend that social businesses are an effective response for three reasons: 1) it helps to deepen the awareness of the contradictions of capitalism and its model of thinking; 2) it illustrates a model of innovation in the area of transitions to sustainability; and 3) it is a practical experience to advance a more democratic business governance and more genuinely business responsibility.